Does the pressure dependence of kinetic isotope effects report usefully on dynamics in enzyme H‐transfer reactions?. (29th January 2015) - Hoeven, Robin; Heyes, Derren J.; Hay, Sam; Scrutton, Nigel S.
<x xml:space="preserve">Abstract</x> The temperature dependence of kinetic isotope effects (KIEs) has emerged as the main experimental probe of enzymatic H‐transfer by quantum tunnelling. Implicit in the interpretation is a presumed role for dynamic coupling of H‐transfer chemistry to the protein environment, the so‐called 'promoting motions/vibrations hypothesis'. This idea remains contentious, and others have questioned the importance and/or existence of promoting motions/vibrations. New experimental methods of addressing this problem are emerging, including use of mass‐modulated enzymes and time‐resolved spectroscopy. The pressure dependence of KIEs has been considered as a potential probe of quantum tunnelling reactions, because semi‐classical KIEs, which are defined by differences in zero‐point vibrational energy, are relatively insensitive to kbar changes in pressure. Reported combined pressure and temperature (p‐T) dependence studies of H‐transfer reactions are, however, limited. Here, we extend and review the available p‐T studies that have utilized well‐defined experimental systems in which quantum mechanical tunnelling is established. These include flavoproteins, quinoproteins, light‐activated enzymes and chemical model systems. We show that there is no clear general trend between the p‐T dependencies of the KIEs in these systems. Given the complex nature of p‐T studies, we conclude that computational simulations using determined (e.g. X‐ray) structures are also needed alongside experimental measurements of reaction rates/KIEs to guide the interpretation of p‐T effects. In providing new insight into H‐transfer/environmental coupling, combined approaches that unite both atomistic understanding with experimental rate measurements will require careful evaluation on a case‐by‐case basis. Although individually informative, we conclude that p‐T studies do not provide the more generalized insight that has come from studies of the temperature dependence of KIEs.